Non-chondritic HSE budget in Earth's upper mantle evidenced by abyssal peridotites from Gakkel ridge (Arctic Ocean) - Liu, Chuan Zhou; Snow, Jonathan E.; BrÃ¼gmann, Gerhard; Hellebrand, Eric; Hofmann, Albrecht W. (Earth and Planetary Science Letters, 2009)
Constraints on the highly siderophile element (HSE: including Os, Ir, Ru, Pt, Pd and Re) budget of the upper mantle upwelling beneath mid-ocean ridges have until now been based on samples that have experienced varying degrees of alteration, partial melting and secondary igneous processes. Here we present results from a set of abyssal peridotites that have been relatively unaffected by these phenomena. Eighteen abyssal peridotites from two localities along the ultra-slow spreading Gakkel Ridge (Arctic Ocean) were selected for this study. Samples from one locality (PS66-238) are extremely fresh, while those from HLY0102-D70 are typical abyssal serpentinites. Comparison of HSE data between fresh peridotites and weathering products supports the contention that HSE are stable during serpentinization, but that Pd and Re are mobile during subsequent weathering. HSE budgets of spinel lherzolites suggest that all platinum group elements (PGEs: including Os, Ir, Ru, Pt and Pd) are compatible during very low degree of partial melting (5-8%), whereas Re behaves as an incompatible element. Harzburgites from each locality were subjected to ~ 12% fractional partial melting, which is lower than that expected for total consumption of sulfides in mantle peridotites (ca. 16%). The harzburgites are depleted in PPGE (Pt, Pd) and Re relative to IPGE (Os, Ir, Ru), which reflects the extraction of sulfide melt along with the silicate melt. Low bulk-rock contents of both Na2O and TiO2 in the fresh PS66-238 lherzolites indicate that they were not transformed from harzburgites through melt refertilization, but represent pristine fertile mantle rocks. Their systematic suprachondritic Ru/Ir and Pd/Ir ratios, but chondritic Pt/Ir ratios, cannot be ascribed to partial melting or secondary igneous processes. This signature may reflect the primary HSE signature of the Earth's upper mantle. Non-chondritic HSE patterns discovered in PS66-238 lherzolites are consistent with the primitive upper mantle (PUM) inferred from the study of orogenic ...